2015
DOI: 10.1002/ajh.24111
|View full text |Cite
|
Sign up to set email alerts
|

Second allogeneic hematopoietic cell transplantation for graft failure: Poor outcomes for neutropenic graft failure

Abstract: Purpose Graft failure (GF) after hematopoietic cell transplant (HCT) occurs in 5 – 30% of patients. GF can be accompanied by neutropenia (NGF) or can result with adequate neutrophils, but loss of donor chimerism (non-neutropenic graft failure, NNGF). In this report we describe the outcomes of 95 patients treated with a second HCT for GF at the University of Minnesota; 62 with NGF and 33 with NNGF. Findings The cumulative incidence of neutrophil recovery at 42 days after second HCT was 45% for NGF and 88% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
(25 reference statements)
5
20
0
2
Order By: Relevance
“…Many regimens used for second HCTs have resulted in poor engraftment and high mortality. Repeat conditioning with fully myeloablative preparative regimens produces unacceptable organ toxicity and risk for overwhelming infections, especially in patients with NGF 9 . Thus, use of a RIC regimen for second HCT represents an attractive and less toxic means of rescue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many regimens used for second HCTs have resulted in poor engraftment and high mortality. Repeat conditioning with fully myeloablative preparative regimens produces unacceptable organ toxicity and risk for overwhelming infections, especially in patients with NGF 9 . Thus, use of a RIC regimen for second HCT represents an attractive and less toxic means of rescue.…”
Section: Discussionmentioning
confidence: 99%
“…By permitting mixed or progressive donor engraftment, RIC HCTs avoid the anticipated prolonged period of aplasia associated with more intensive myeloablative regimens. A major concern with using RIC regimens for salvage HCT has been an increased rate of second GF, which is of particular concern in a patient who has previously experienced GF following first transplantation 9 . Our NMA conditioning regimen utilizes fludarabine to provide appropriate immunosuppressive conditioning; while combination of low dose busulfan and low dose TBI allows for adequate myeloablation to ensure engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Previous retrospective studies however have demonstrated a generally poor outcome following second transplant for graft failure. [12][13][14] Data concerning second allogeneic HCT in the literature are scarce and are generally limited to retrospective studies with limited numbers of patients. The purpose of this study was to retrospectively investigate the parameters that influence post-second allogeneic HCT survival at our center, as well as to characterize the post-transplant course of survivors in regard to post-transplant complications and performance status.…”
mentioning
confidence: 99%